2022
DOI: 10.1155/2022/1877960
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic Value of the Triple Combination of Serum Heparin-Binding Protein, Procalcitonin, and C-Reactive Protein in Children with Acute Bacterial Upper Respiratory Tract Infection

Abstract: To investigate the role of the triple combination serum heparin-binding protein (HBP), procalcitonin (PCT), and C-reactive protein (CRP) in children with acute bacterial upper respiratory tract infection (ABURTI). A total of 130 children with upper respiratory tract infection admitted to the Department of Pediatrics of Fujian Maternity and Child Health Hospital from September 2019 to January 2021 were selected as the research group. According to the results of pathogenic analysis, children were further subdivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…HBP has been previously reported to have a clear diagnostic value in children with acute bacterial infection [20]. The present study revealed that HBP can also be useful for older patients with HAP.…”
Section: Discussionsupporting
confidence: 62%
“…HBP has been previously reported to have a clear diagnostic value in children with acute bacterial infection [20]. The present study revealed that HBP can also be useful for older patients with HAP.…”
Section: Discussionsupporting
confidence: 62%
“…Hence, the use of multiple biomarkers, including sTREM-1, can accurately help to distinguish VAP patients from those not affected by any pulmonary infection [20]. HBP has been previously reported to have a clear diagnostic value in children with acute bacterial infection [21]. The present study revealed that HBP can also be useful for older patients with HAP.…”
Section: Discussionmentioning
confidence: 51%
“…HBP has been previously reported to have a clear diagnostic value in children with acute bacterial infection [ 21 ]. The present study revealed that HBP can also be useful for older patients with HAP.…”
Section: Discussionmentioning
confidence: 99%
“…This combined diagnostic score can guide the clinical formulation of a reasonable treatment plan. Yang et al 28 also used a triad of serum inflammatory markers to diagnose acute bacterial upper respiratory tract infections in children. This combined diagnostic score is expected to be a potential predictor of outcome.…”
Section: Discussionmentioning
confidence: 99%